Analyzing numeracy skills of upper primary graders in real-world problem contexts - Akmal, Nurul; Idris, Khairiani; Fauziana, Fauziana; Harun, Jamilah (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2025)
Numeracy skill is a critical skill for elementary school students, enabling them to apply mathematical concepts in everyday contexts and make informed decisions. This study investigates the numeracy skills of 55 fifth-grade students from Lhokseumawe City, Aceh Province. The students’ numeracy skills were measured across three key indicators: counting, numerical relations, and arithmetic operations. A descriptive quantitative approach was used to assess students' abilities. The results indicated that while students performed well in basic counting and arithmetic tasks, they struggled with tasks involving numerical relations and distinguishing quantities. The highest performance was observed in "counting an object verbally" (73%), while the lowest average score was in "distinguishing the quantity of an object" (41%). The study emphasizes the importance of integrating real-life scenarios into math instruction to improve numeracy skills. It also highlights the need for teacher training, scaffolded learning strategies, and the incorporation of higher-order thinking skills (HOTS) in the curriculum. The findings offer valuable insights for educators and policymakers aiming to enhance numeracy skills in elementary education, with implications for both academic performance and practical application.